The rise and evolution of COVID-19 - Baghchechi, Mohsen (Int J Womens Dermatol, 2020)
Coronaviridae (CoV) is a large family of zoonotic viruses linked to a range of diseases from the common cold to severe acute and Middle East respiratory syndrome CoV epidemics. In 2019, a novel virus emerged from Wuhan, China, and resulted in a marked worldwide outbreak of respiratory illness. Prevention and containment became the prioritized intervention against COVID-19, coupled with a continued search for hallmarks of the disease that would allow early detection and provide insight into management and triage. Cutaneous findings associated with COVID-19 include diffuse maculopapular rashes, livedo reticularis, and acro-ischemic “COVID toes.” These skin findings occurred anywhere from days before respiratory symptom onset to weeks after recovery, and predominantly in child and adolescent populations. The role of dermatologists can be expanded during this COVID-19 pandemic to help identify disease through cutaneous presentations.